2022
DOI: 10.1111/ajo.13515
|View full text |Cite
|
Sign up to set email alerts
|

The use of the myometrial‐cervical ratio in the ultrasound diagnosis of adenomyosis – A validation study

Abstract: Background Adenomyosis is a benign disorder defined by ectopic endometrial glands within the uterine myometrium. A study by Mooney et al reported the myometrial‐cervical ratio (MCR), a novel ultrasound measurement that was found to improve the preoperative diagnosis of adenomyosis. Aims To validate the association between sonographic MCR and adenomyosis confirmed on histopathology in an independent patient group. Materials and Methods Single‐centre retrospective cohort study including women who underwent hyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Ongoing research into developing imaging tools to aid in diagnosing adenomyosis preoperatively, could help provide a diagnosis for women experiencing pelvic pain and heavy menstrual bleeding, and in turn further clarify clinical features and effectiveness of non-surgical management options of adenomyosis. Overall, this study demonstrates that the MCR has lower accuracy in diagnosing adenomyosis pre-operatively, as was shown previously by Mooney et al 9 and McCaughey et al 10 However, in the regional setting, where due to resources pre-operative ultrasound diagnosis of adenomyosis is uncommon, the MCR may be a useful adjunct, as it outperformed the traditional non-specialist sonographic measures. In the absence of fibroids, the MCR sensitivity was 71.4% and specificity 60.0% using the cutpoint of 1.875.…”
Section: Discussionsupporting
confidence: 76%
“…Ongoing research into developing imaging tools to aid in diagnosing adenomyosis preoperatively, could help provide a diagnosis for women experiencing pelvic pain and heavy menstrual bleeding, and in turn further clarify clinical features and effectiveness of non-surgical management options of adenomyosis. Overall, this study demonstrates that the MCR has lower accuracy in diagnosing adenomyosis pre-operatively, as was shown previously by Mooney et al 9 and McCaughey et al 10 However, in the regional setting, where due to resources pre-operative ultrasound diagnosis of adenomyosis is uncommon, the MCR may be a useful adjunct, as it outperformed the traditional non-specialist sonographic measures. In the absence of fibroids, the MCR sensitivity was 71.4% and specificity 60.0% using the cutpoint of 1.875.…”
Section: Discussionsupporting
confidence: 76%
“…Before our study, Mooney et al investigated the diagnostic accuracy of the ratio between antero-posterior diameters of uterus and cervix, named myometrial-cervical ratio, in a series of pre- and post-menopausal women undergone hysterectomy for benign non obstetric conditions [ 19 ]. Despite promising results in their first retrospective study, validation prospective study on women requiring hysterectomy revealed low accuracy, sensitivity and specificity, in particular when fibroids were not excluded in the calculation of the uterine AP diameter [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are poor data and controversial results on diagnostic performance of some quantitative biometrical parameters that can differentiate adenomyosis uteri from non-adenomyosis ones [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…23 The ratio of AD to cervical canal thickness (the myometrial-cervical ratio) was also reported to be associated with a histological diagnosis of adenomyosis. 24,25 These results together suggested that the increment of AD is more important than other diameters in adenomyosis. It was observed that early adenomyosis evolves in the sagittal midline of the mid-corporal and fundal part of the uterus under MRI and TVS.…”
Section: Discussionmentioning
confidence: 80%
“…Other researches also reported that among simple and complex uterine biometric parameters such as diameters and their ratios, uterine AD showed the best combination of sensitivity and specificity in differentiating uteri with adenomyosis defined by the Morphological Uterus Sonographic Assessment (MUSA) criteria 23 . The ratio of AD to cervical canal thickness (the myometrial–cervical ratio) was also reported to be associated with a histological diagnosis of adenomyosis 24,25 . These results together suggested that the increment of AD is more important than other diameters in adenomyosis.…”
Section: Discussionmentioning
confidence: 84%